Disciplina / Indisciplina: sentidos e significados constituídos por docente do ensino fundamental na educação cristã - Wolff, Jaime da Silva (2015)
The goal of this study is to learn the senses and meanings constituted by the discipline/indiscipline in the educational process by a 5th grade elementary school teacher in private education (adventist). The character of the study is qualitative and has followed the socio-historic theory assumptions, using the sense and meaning categories as priorities. A teacher from a Christian private school was part of the study. The data was collected through semi-structured interviews in the current modality, consisting of three interviews with the same subject with the goal of qualifying information. The statements were bonded in pre-indicators, and those were collected in indicators and finally they were articulated in four signification cores constituted as: the teaching choice; the teaching method; dealing with the discipline/indiscipline and the Christian philosophy. It is present in the participant s statements that her teaching practice is permeated by the classic/traditional of discipline/indiscipline, having also an attempt to conceive an ethical and dialogic subject, by means of an education that aims, as the ideal, the student s intellectual autonomy. The debate around the discipline/indiscipline theme is still permeated by dogmas and myths that restrict its comprehension. In this sense, the discipline needs to be understood as a learned construction in and by the activities involved in the teaching-learning process, which involves social interaction and consists of learning manners appropriation that lead to acting, thinking and feeling autonomy, the education s goals